THE COMPOSITION OF THE MAIN AND SIDE CATCHES ON THE PURSE SEINERS(PURSE SEINE) FISHING GEAR IN THE BUNGUS OCEAN FISHING PORT - Riau Firnanda AR; Pareng Rengi; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Purse seine is considered to be the most productive fishing gear to catch pelagic fish, so that in 2014-2017 there were 50 units of ships carrying out loading at the Samudera Bungus Oceanic Fishing Port operate in the Fisheries Management Area  of the Republic of Indonesia (WPP 572) with the largest production of catches 887.124 Kg, but in conducting an arrest operation have you got the optimal catch. Because during this time the operation of the arrest was only determined based on experience. This study aims to determine the composition of the catch purse seine based on the main and side catches and to know the pattern of the catching season. The method used is a direct survey method which includes primary and secondary data containing the last 4 years (2014-2017) obtained from the Bungus Ocean Fishing Port. The catches during the study were 10 types of fish: fish cakalang (Katsuwonus pelamis), tongkol krei (Auxisthazard),madidihang (Thunnus albacares), mata besar (Thunnus obesus), lisong (Auxis rochei), sunglir (Elagatis bipinulatus), lemadang (Coryphaena hippurus) as the main catch (Main catch). Whereas fish layang (Decapterus macrosoma), layaran (Istiophorus oriantalis), baby tuna (Euthynnus alletteratus)is a side  (by-catch). Keywords: composition of the catch, purse seiners, fishing season